Socialization and Counseling for Students of Al Razi Sinar Harapan Medan Private Vocational High School on the Proper Use of Antibiotics to Prevent Drug Resistance - Aritonang, Barita; Syarifuddin, Shofian; Widyaningsih, Fadlilah; Panjaitan, Delita; Pitriani, Pitriani (JURNAL PENGMAS KESTRA (JPK), 2023)
To address global challenges related to drug resistance, the role of universities as centers of knowledge and innovation becomes a key driver in overcoming this issue. Universities are expected to actively carry out the three pillars of education, research, and community service. A concrete example of implementing these pillars is through awareness and education activities for students at Al Razi Sinar Harapan Medan Private Vocational High School regarding the appropriate use of antibiotics to prevent drug resistance. These awareness and education activities aim to provide a deep understanding to students about the judicious use of antibiotics as a preventive measure against drug resistance. The methods employed include lectures through presentations, group discussions, and question-and-answer sessions. To assess the level of understanding among students at Al Razi Sinar Harapan Medan Private Vocational High School regarding the use of antibiotics, an evaluation was conducted using a questionnaire. Based on the questionnaire results, before the awareness and education activities on the correct and proper use of antibiotics, the knowledge level of students at Al Razi Sinar Harapan Medan Private Vocational High School was low. However, after participating in these activities, there was a significant improvement in the students' knowledge about the more appropriate and accurate use of antibiotics. Students who gained this knowledge became more skilled and informed in managing their health, fostering a sense of responsibility for personal and community health. Thus, these awareness and education activities not only directly benefit the students' knowledge but also have a broader positive impact on public health as a whole. This effort is expected to make a positive contribution to reducing irrational antibiotic use and minimizing the impact of drug resistance among students, while also supporting the university's Tridarma vision to create a healthier and smarter society. The conclusion drawn from these activities is that students at Al Razi Sinar Harapan Medan Vocational High School now have a better understanding of antibiotic use and are aware of the risks of drug resistance.